2022
DOI: 10.2215/cjn.03840322
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Donor-Derived Cellfree DNA in Pediatric Kidney Transplantation

Abstract: Background and objectivesDonor-derived cellfree DNA (cfDNA) is a less-invasive marker of allograft injury compared with kidney biopsy. However, donor-derived cfDNA has not yet been extensively tested in children, where the test may have different characteristics.Design, setting, participants, & measurementsWe assayed donor-derived cfDNA (AlloSure; CareDx) from 290 stored plasma samples from a prospective biobank at our center, collected from 57 children monthly in the first year postkidney transplant betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In our cohort of pediatric kidney transplant recipients, a dd‐cfDNA level of >1% was associated with BPAR, consistent with the published literature examining dd‐cfDNA in kidney transplantation, despite no change in CrCl 6,14 . We also found that dd‐cfDNA levels were higher in patients with AMR compared to those with TCMR, consistent with other studies 15 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our cohort of pediatric kidney transplant recipients, a dd‐cfDNA level of >1% was associated with BPAR, consistent with the published literature examining dd‐cfDNA in kidney transplantation, despite no change in CrCl 6,14 . We also found that dd‐cfDNA levels were higher in patients with AMR compared to those with TCMR, consistent with other studies 15 .…”
Section: Discussionsupporting
confidence: 91%
“…However, the low sensitivity for diagnosing rejection may preclude dd-cfDNA from being used as the sole screening tool, as suggested by Chang et al 16 Different dd-cfDNA cutoffs have been examined with varying results. Dandamudi et al 14 found that at a dd-cfDNA cutoff of >0.5% to diagnose rejection, the sensitivity improved to 78% but specificity decreased to 79%, similar to our cohort. In the ADMIRAL study, investigators evaluated the use of dd-cfDNA monitoring in 1092 adult kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations